Stable carbon (delta(13)C) and nitrogen (delta(15)N) isotopes as natural indicators of live and dry food in Piaractus mesopotamicus (Holmberg, 1887) larval tissue - Jomori, Rosangela Kiyoko [UNESP]; Ducatti, Carlos [UNESP]; Carneiro, Dalton Jose [UNESP]; CeliaPortella, Maria [UNESP] (Wiley-Blackwell, 2008)
This study proposed the use of the stable isotope technique to track the type of food utilized by pacu Piaractus mesopotamicus larvae during their development, and to identify the moment when the larvae start using nutrients from the dry diet by retaining its carbon and nitrogen atoms in their body tissues. Five-day-old pacu larvae at the onset of exogenous feeding were fed Artemia nauplii or formulated diet exclusively; nauplii+formulated diet during the entire period; or were weaned from nauplii to a dry diet after 3, 6 or 12 days after the first feeding. delta(13)C and delta(15)N values for Artemia nauplii were -15.1 parts per thousand and 4.7 parts per thousand, respectively, and -25.0 parts per thousand and 7.4 parts per thousand for the dry diet. The initial isotopic composition of the larval tissue was -20.2 parts per thousand and 9.5 parts per thousand for delta(13)C and delta(15)N respectively. Later, at the end of a 42-day feeding period, larvae fed Artemia nauplii alone reached values of -12.7 parts per thousand and 7.0 parts per thousand for delta(13)C and delta(15)N respectively. Larvae that received the formulated diet alone showed values of -22.7 parts per thousand for delta(13)C and 9.6 parts per thousand for delta(15)N. The stable isotope technique was precise, and the time at which the larvae utilized Artemia nauplii, and later dry diet as a food source could be clearly defined.
Keywords: pacu Piaractus mesopotamicus (Holmberg 1887); live food; dry diet; larval feeding; stable carbon (delta(13)C) isotope; stable nitrogen (delta(15)N) isotope